Greece’s Ethnic Cleansing Operation to the Turks as a War Crime in East Thrace 1920 -1922 - Mehmet Şükrü Güzel (Gazi Akademik Bakış)
Greek goverment policy was to force to immigrate the majority of the population, the Turks in the occupied lands of Anatolia and East Thrace. The policy of Greek goverment can only be described as barbarism. Greek goverment used methods of forced expropriation of Turkish lands and houses with out any indemnity, burned Turkish villages and towns, killed Turkish civilians and forced others to leave their houses. Greek goverment made mass tranfer of the Greeks living in Cacause and resettled them in Turkish homes. Greek goverment settled around 100.000 Cacause Greeks in East Thrace. More then 30.000 Turkish villagers took refuge in Bulgaria to save their lives. Also around 60.000 Turkish villagers escaped to İstanbul to save their lives. Greek Goverment in August 1922 gave the order to all Turks to leave their houses who were living between the Bulgarian frontier and Çatalca numbered around 270.000. Now today, the policy of Greek goverment is called as “ Ethnic Cleansing “. Also according to the 4th Convention of the Hague 1907, the polices of Greek goverment as an occupied force must be accepted as the war crimes act.